Everybody thought we were crazy : Dennis Hopper, Brooke Hayward, and 1960s Los Angeles - Rozzo, Mark (Ecco, an imprint of HarperCollinsPublishers, 2022)
"Los Angeles in the 1960s: riots in Watts and on the Sunset Strip, wild weekends in Malibu, late nights at The Daisy discotheque, openings at the Ferus Gallery, and the convergence of pop art, rock and roll, and the New Hollywood. At the center of it all, one inspired, improbable, and highly combustible couple-Dennis Hopper and Brooke Hayward-lived out the emblematic love story of '60s L.A. The home these two glamorous young actors created for themselves and their family at 1712 North Crescent Heights Boulevard in the Hollywood Hills became the era's unofficial living room, a kaleidoscopic realm-"furnished like an amusement park," Andy Warhol said-that made an impact on anyone who ever stepped into it. Hopper and Hayward, vanguard collectors of contemporary art, packed the place with pop masterpieces by the likes of Roy Lichtenstein, Ed Ruscha, and Warhol, and welcomed a who's who of visitors, from Jane Fonda to Jasper Johns, Joan Didion to Tina Turner, Hells Angels to Black Panthers. In this house, everything that defined the 1960s went down: the fun, the decadence, the radical politics, and, ultimately, the danger and instability that Hopper explored in the project that made his career, became the cinematic symbol of the period, and blew their union apart-Easy Rider. Everybody Thought We Were Crazy is at once a fascinating account of the Hopper and Hayward union and a deeply researched, panoramic cultural history. It's the intimate saga of one couple whose own rise and fall-from youthful creative flowering to disorder and chaos-mirrors the very shape of the decade"--